Happiness Curriculum: From the State- Delhi - Parashar, Kapila (THE PRIMARY TEACHER, 2019)
Students study ‘Happiness Curriculum’ in the schools run by the Directorate of Education, Delhi, as part of their formal education. This unique and innovative curriculum was introduced in the year 2018 to humanise the school education. The focus of the curriculum is to introduce and develop the concept of sustainable happiness in students studying in Classes Nursery to VIII of the Directorate of Education, Delhi. The curriculum promotes leading by example rather than preaching.